THE POWER OF COMMAS IN SHAPING THE ENGLISH LANGUAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the critical role of the comma in shaping the English language from grammatical, historical, legal, and stylistic perspectives. Tracing its origins to Ancient Greek rhetoric, the comma has evolved into a powerful syntactic tool essential for clarity, pacing, and meaning in both written and spoken English. The article discusses the grammatical functions of commas, such as separating clauses and clarifying ambiguity, and delves into the ongoing debate over the Oxford comma, including its real-world legal implications. Additionally, the stylistic use of commas in literature and creative writing is examined, highlighting their influence on tone and rhythm. The challenges of teaching comma usage to English language learners are also addressed. Supported by linguistic and pedagogical research, the article affirms that while small in form, the comma holds significant power in communication and interpretation.